1. The problem statement, all variables and given/known data In the Pauli theory of the electron, one encounters the expresion: (p - eA)X(p - eA)ψ where ψ is a scalar function, and A is the magnetic vector potential related to the magnetic induction B by B = ∇XA. Given that p = -i∇, show that this expression reduces to ieBψ. 2. Relevant equations pXp = 0 and AXA = 0 3. The attempt at a solution I've come to this: -e(pXA + AXp)ψ but I don't even have a clue where to go next since, for all I know, pXA + AXp = -(AXp) + AXp = 0 ? Someone's got a clue what I should do next? Am I missing something here?